Tourism Communication Model Based on Local Wisdom: Qualitative Descriptive Research in Gunung Padang, Cianjur Regency - Andri, Andri; Dunan, Amri (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Gunung Padang is a tourist destination with unique beauty and uniqueness in the Karyamukti Village area, Campaka District, Cianjur Regency, West Java Province. The concept of conveying tourism information based on regional distinctiveness is traditional or local cultural activities that are still practiced in an area. In the development of tourism destinations, there is a pattern of interaction that exists between stakeholders, both between groups, groups with individuals, or individuals with groups. This study aims to describe the form of information delivery with regional distinctiveness at the Gunung Padang Cultural Heritage Site and analyze tourism communication between stakeholders, such as stakeholders and residents, related to efforts to develop regional tourism. This study uses qualitative research methods. Tourism communication at the Gunung Padang Cultural Heritage Site involves various institutions such as the Department of Culture and Tourism of Cianjur Regency, the Cultural Heritage Preservation Center of Banten, and the Tourism Department of West Java Province. This necessitates a longer bureaucracy and coordination process for tourism management. The Department of Culture and Tourism consistently seeks input from managers and the local community in formulating policies for developing tourism efforts at the Gunung Padang Cultural Heritage Site to ensure the successful implementation of programs.